Prehospital administration of broad‐spectrum antibiotics for sepsis patients: A systematic review and meta‐analysis. Issue 3 (1st April 2022) - Varney, Joseph; Motawea, Karam R.; Kandil, Omneya A.; Hashim, Hashim T.; Murry, Kimberly; Shah, Jaffer; Shaheen, Ahmed; Akwari, Joy; Awad, Ahmed K.; Rivera, Amanda; Mostafa, Mostafa R.; Swed, Sarya; et al.
Abstract: Background and Aims: Some studies have suggested that earlier initiation of antibiotics has shown positive outcomes in sepsis patients. We aimed to do a systematic review and meta‐analysis to evaluate the effect of prehospital administration of antibiotics on 28 days mortality and length of stay in hospital and intensive care unit for sepsis patients. Methods: We formulated a search strategy and used it on search databases PubMed, Scopus, Web of Science, and Embase. We then screened the records for eligibility and included controlled studies, either clinical trials or cohort studies reporting prehospital antibiotic administration for sepsis patients. We excluded duplicates, books, conferences' abstracts, case reports, editorials, letters, author responses, not English studies, and studies with nonavailable full text. Animal and lab studies were also excluded. Results: The total number of studies identified is 1811, 19 were eligible for systematic review and 4 for meta‐analysis (three cohort and one clinical trial). The total number of sepsis patients in the four included studies in the 28 days mortality outcome was 3523 (1779 took prehospital antibiotics and 1744 did not take prehospital antibiotics). Of 1779 who took the antibiotics, 190 died, and of 1744 who did not take antibiotics, 292 died (95% confidence interval 0.68–0.97, p  = 0.02). Conclusion: This meta‐analysis reveals that receiving prehospital antibiotics can significantly lower mortality in sepsis patients compared to patients who do not receive prehospital antibiotics. However, more clinical trials and multicenter prospective studies with high sample sizes are needed to get strong evidence supporting our findings.